A novel fluorescent probe, triphenylamine rhodamine-3-acetic acid (mRA) for the detection of Amyloid-β aggregates in Alzheimer's disease - Chinnappan, Raja; Khan, Mateen A.; Mohammad, Taj; Allwaibh, Sarah Mohammed; Easwaramoorthi, Shanmugam; Yaqinuddin, Ahmed; Devansan, Sandhanasamy; Mir, Tanveer Ahmad; Hassan, Imtaiyaz (Frontiers in Neuroscience, 2025)
Amyloid-β (Aβ) is implicated in the pathophysiology of Alzheimer's disease (AD) and plays a significant role in neuronal degeneration. Aβ in solution is essential during the initial stages of developing lead compounds that influence Aβ fibrillation. The tendency of the Aβ peptide to misfold in solution is correlated with the etiology of AD. Therefore, the early detection of Aβ serves as a critical foundation for diagnostic testing and routine clinical assessment of AD. Herein, an aggregation-induced fluorescence probe, triphenylamine rhodamine-3-acetic acid (mRA), was used to detect Aβ aggregates. The fluorescence results showed a strong interaction between the fluorescence probe mRA and Aβ aggregates. mRA specifically binds with high affinity to Aβ aggregates, and the limit of detection (LOD) of Aβ aggregates was 0.12 μg/mL. Molecular docking studies showed that the mRA has significant binding affinity toward the Aβ peptide at the N/C-terminal region, with a binding energy of −6.5 kcal/mol. Furthermore, CD studies confirmed that the mRA binds to Aβ aggregates, and its binding induces significant structural alteration of the Aβ aggregates. Thermodynamic properties revealed that the binding of Aβ aggregates to mRA is a spontaneous process, driven by enthalpy and favored by entropy, which helps further our understanding of the interaction between mRA and Aβ aggregates at the molecular level. The negative ΔH suggests that hydrogen bonding is a dominant force for the mRA interaction with Aβ aggregates. This study provides a rationale for using mRA as a biosensor for the detection of Aβ aggregates in biological fluids, offering a potential tool for the early diagnosis and monitoring of amyloid progression in AD.